2022
DOI: 10.1111/1471-0528.17145
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of pudendal nerve entrapment after sacrospinous ligament fixation

Abstract: To analyse the efficacy of sacrospinous ligament (SSL) suture removal on the reduction of pain symptoms in the case of suspected pudendal nerve entrapment after sacrospinous ligament fixation (SSLF). Design: Retrospective cohort study.Setting: Tertiary referral centre, the Netherlands.Population: A cohort of 21 women having their SSLF sutures removed because of SSLF-related pain symptoms.Methods: Clinical record review. Main outcome measures:The primary outcome was reduction of pain after SSL suture removal. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…SSLF, a traditional surgery for apical prolapse, has good subjective and objective cure rates (5); however, by many patients experience postoperative complications. Gluteal pain is the most common complication of SSLF (7)(8)(9)(10)(11)(12). In Mowat's study of POP patients who underwent SSLF with the Capio device, 86% reported buttock pain at 1 week, and the incidence had dropped to 16% by the sixth week (9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SSLF, a traditional surgery for apical prolapse, has good subjective and objective cure rates (5); however, by many patients experience postoperative complications. Gluteal pain is the most common complication of SSLF (7)(8)(9)(10)(11)(12). In Mowat's study of POP patients who underwent SSLF with the Capio device, 86% reported buttock pain at 1 week, and the incidence had dropped to 16% by the sixth week (9).…”
Section: Discussionmentioning
confidence: 99%
“…In Mowat's study of POP patients who underwent SSLF with the Capio device, 86% reported buttock pain at 1 week, and the incidence had dropped to 16% by the sixth week (9). Nonsteroidal anti-inflammatory drugs (NSAIDs), local anesthesia, or surgical management are used to treat gluteal pain in some patients after SSLF (11)(12)(13)(14). In Katrikh's study, the S4 nerve root was found in the medial third of the SSL in 96% (43/45) of cadaveric specimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dear Dr. Papageorghiou, We read with interest 'Surgical management of pudendal nerve entrapment after sacrospinous ligament fixation' by Vodegel et al in your journal. 1 We commend the authors on reviewing this poorly understood but debilitating complication. However, we would appreciate further clarification.…”
Section: More Answers Are Needed Before Proposing Surgical Management...mentioning
confidence: 99%
“…Dear Dr. Papageorghiou, We would like to thank Dr Okeahialam and colleagues for their kind words and valuable comments on our article 'Surgical management of pudendal nerve entrapment after sacrospinous ligament fixation'. 1,2 Dr Okeahialam and colleagues wonder how the 'complete removal' of absorbable sutures is possible. For clarification, in the Netherlands it is common practice to use Prolene® sutures, which are non-absorbable.…”
mentioning
confidence: 99%